Crafting Effective HRM Strategies for Enhancing Organizational Performance and Employee Engagement - Humairah, Kuraisyah Al; Irawan, Andri; Ibrahim, Muhdi B. Hi; Yendra, Yendra; Rasyid, Abdul (Yayasan Pendidikan Bukhari Dwi Muslim, 2023)
Purpose: This study examines the effectiveness of Human Resource Management (HRM) strategies in enhancing organizational performance and employee engagement, addressing gaps in HRM customization for specific organizational needs. Research Design and Methodology: Utilizing a qualitative approach, the research involves semi-structured interviews and document analysis to collect data from a purposive sample of HR professionals, managers, and employees. This exploratory and interpretive study aims to deeply understand the impacts of tailored HRM practices. Findings and Discussion: Key findings reveal the importance of high-performance work practices and strategic HR alignment in boosting organizational performance. The study also highlights the critical roles of organizational culture and leadership styles in enhancing employee engagement and effective HRM strategy implementation. Internal communication quality within organizations significantly affects HRM outcomes. Implications: The study suggests aligning HRM strategies with business goals and enhancing workplace environments to foster employee engagement. These findings contribute to HRM theoretical frameworks and offer practical insights for HR professionals in designing effective, context-specific strategies. Future research should explore these relationships in diverse organizational contexts to optimize HRM practices further.